„I ride with you“ – active promotion of mental health in Bulgaria - K. Guevara (European Psychiatry, 2022)
Introduction One of the main concepts of mental health promotion is proactivity, rather than reactivity. As psychiatrists we must be the first line of mental health advocacy and to do so we must share clear messages and take definitive actions.